Investigation of usage, attitudes toward complementary and alternative medicine among cancer patients in Turkey during the COVID-19 pandemic - Genc, Ezgi; Bulut, Irem (Ios Press, 2024)
BACKGROUND: Complementary and alternative medicines (CAM) are being uses more often with cancer patients. OBJECTIVE: This study aimed to investigate attitudes, use and influencing factors of CAM among cancer patients during the COVID-19 pandemic. METHODS: This descriptive, cross-sectional study was conducted on 407 cancer patients in Turkey. The study was conducted during July-September 2021 using a Questionnaire that included a Complementary, Alternative and Conventional Medicine Attitude Scale (CACMAS). Pearson's Chi-Squared Test, Mann-Whitney U, Kruskal Wallis, and logistic regression were all utilized. RESULTS: The findings revealed that 76.2% of the participants stated that they used CAM methods while undergoing cancer treatment, and 65.2% of those who did so kept from sharing this information to medical professionals. Phytotherapy was the most common CAM method used by patients. The use of CAM was found to be significantly higher among those who were 55-64 years of age, married, secondary school graduates, non-smokers, CAM users before their cancer diagnosis, and who had a family history of cancer (p p < 0.05). The participants' average CACMAS scores were 112.20 +/- 16.53. Among those who used CAM during treatment, non-smoking, overweight-obese participants had higher CACMAS scores (p p < 0.05). CONCLUSION: Due to the high prevalence of CAM usage among cancer patients and possible interaction effects with chemotherapy medications, it is important for healthcare professionals to assess and educate cancer patients regarding CAM use. Additional research is needed to determine potential interactions, as well as pros and cons of CAM use during cancer treatment.
Keywords: Attitude; complementary therapies; COVID-19; neoplasms; patients; phytotherapy; traditional medicine